2023
DOI: 10.1111/hdi.13068
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of transitional care units on dialysis patient outcomes: A multicenter, propensity score‐matched analysis

Abstract: Introduction Inadequate predialysis care and education impacts the selection of a dialysis modality and is associated with adverse clinical outcomes. Transitional care units (TCUs) aim to meet the unmet educational needs of incident dialysis patients, but their impact beyond increasing home dialysis utilization has been incompletely characterized. Methods This retrospective study included adults initiating in‐center hemodialysis at a TCU, matched to controls (1:4) with no TCU history initiating in‐center hemod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A prior scoping review identified PD-first policies, modality education programs, and audit and feedback, providing assisted PD, transitional care units, and bedside catheter placement as interventions that have been associated with increased PD utilization. 49,50 It is important to note that most of these studies looking at patient-level and provider-level interventions came from single centers, lacked control groups, were implemented in centers with low PD penetration at baseline, or involved restricting patient choice. At the policy level, PD-first policies in Hong Kong and Thailand have been associated with an increase in the numbers of patients treated with PD.…”
Section: Strategies For Increasing Home Dialysis Utilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A prior scoping review identified PD-first policies, modality education programs, and audit and feedback, providing assisted PD, transitional care units, and bedside catheter placement as interventions that have been associated with increased PD utilization. 49,50 It is important to note that most of these studies looking at patient-level and provider-level interventions came from single centers, lacked control groups, were implemented in centers with low PD penetration at baseline, or involved restricting patient choice. At the policy level, PD-first policies in Hong Kong and Thailand have been associated with an increase in the numbers of patients treated with PD.…”
Section: Strategies For Increasing Home Dialysis Utilizationmentioning
confidence: 99%
“…54 The use of transitional care units where a 4-week educational intervention was delivered was associated with an increase in home dialysis utilization in Fresenius Medical Care units in the United States. 50 In Canada, the Ontario Renal Network introduced a modality-based funding formula, mandatory informatics system, and targets for prevalent home dialysis rates, and then conducted frequent meetings with nephrology programs to review progress. They funded home dialysis coordinators, encouraged and funded assisted PD, and provided support for catheter insertion and urgent start PD.…”
Section: Strategies For Increasing Home Dialysis Utilizationmentioning
confidence: 99%
“…49,50 Among other outcomes, a recent multicenter study showed that patients going through TCU programs were 2.5 times more likely to convert to home dialysis, making them an important part of home dialysis growth in the future. 51…”
Section: Transitional Care Unitsmentioning
confidence: 99%
“…27 Another review demonstrated higher likelihood of arteriovenous access and transplant referral at 14 months after enrollment. 33 Community House HD A community house for hemodialysis (CHH) is a facility where patients are able to receive HD in a shared space away from the in-center HD unit. Unlike community or satellite dialysis units, patients perform HD independently in a home-like environment, without the assistance or direct supervision of medical personnel.…”
Section: Infrastructure For Increased Home Dialysis Utilizationmentioning
confidence: 99%
“…27 Another review demonstrated higher likelihood of arteriovenous access and transplant referral at 14 months after enrollment. 33…”
Section: Infrastructure For Increased Home Dialysis Utilizationmentioning
confidence: 99%